Growth of Female Mice (Mus musculus) Fed with Mung Beans (Vigna radiata) Based Feed - Anggraini, Dina; Imaniar, Lisana Husna; Istiadi, Khaerunissa Anbar; Mulyana, Jeane Siswitasari; Anisa, Hida Arliani Nur (Universitas Bengkulu, 2025)
Laboratory mice are widely used in biomedical research due to their genetic similarities to humans. The dietary needs of mice in Indonesia. However, they are frequently not satisfied by commercially available feed. This indicates the necessity for locally obtained, customized feed formulations, like those that include mung beans, which are high in vital nutrients and promote sustainable agriculture. This study aims to compare the effect of various mung bean-based feeds on the weight gain of female mice and their feed conversion value. Four feed formulations with varying concentrations of mung beans (85%, 75%, 65%, and 55%) were compared to commercial Broiler II feed, using 20 female mice over two months. The study involved daily feeding, weighing consumed feed, and mice’s body weight to determine the Feed Conversion Ratio (FCR), and the Kruskal-Wallis test for statistical analysis. The results show no statistical difference between treatments, which means all treatments are comparable to the control groups in promoting mice growth in all the parameters observed. Nevertheless, a certain trend was observed where the higher the mung bean content, the more similar the results to the control group. Thus, treatments MB85 containing 85% mung beans might have the greatest potential to promote mice growth.